454 Brace Brace: Modified Brsotrom-Gould Procedure with and Without Internal Brace for the Treatment of Chronic Lateral Ankle Instability. (4th May 2021) - McGuigan, J; Pillai, A; Hall, A
Abstract: Introduction: The most common ankle injury is a sprain. Surgical management is only indicated when nonoperative treatment fails. Modified Broström-Gould (MBG) is the gold standard surgical technique. MBG technique may be augmented with an internal brace. This study aims to compare the clinical outcomes of MBG with and without internal brace for the treatment of chronic lateral ankle instability using validated patient recorded outcome measures. Method: Retrospective analysis of patients that underwent lateral ankle ligament reconstruction between January 2012 and June 2019 were reviewed at and asked to complete the Manchester oxford foot and ankle questionnaire (MOXFQ). 29 patients (30 ankles) underwent lateral ligament reconstruction between these dates and completed the questionnaire, 20 patients (21 ankles) without internal brace and 9 patients with internal brace. Results: The group with internal brace displayed significantly better results in the MOXFQ summary index score (20.49 ± 13.15 vs 43.53 ± 34.72, P = 0.014) and standing/walking subscale (15.48 ± 13.00 vs 45.92 ± 36.60, P = 0.023) compared to group without internal brace. There was no significant difference between Pain and Social interactions subscales. Conclusions: Our results show that the addition of an internal brace to the MBG procedure for the management of chronic lateral ankle instability improves clinical outcomes.